In the days of our grandmothers: a reader in Aboriginal women's history in Canada - Kelm, Mary-Ellen; Townsend, Lorna (University of Toronto Press, 2006)
From Ellen Gabriel to Tantoo Cardinal, many of the faces of Aboriginal people in the media today are women. In the Days of Our Grandmothers is a collection of essays detailing how Aboriginal women have found their voice in Canadian society over the past three centuries. Collected in one volume for the first time, these essays critically situate Aboriginal women in the fur trade, missions, labour and the economy, the law, sexuality, and the politics of representation. (Midwest).
Keywords: 1700-1799; 1800-1899; 1900-1999; 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; canada; commerce; commerce de peaux; cours; discipline; droit; droits des femmes*; droits des femmes* autochtones; famille; féminisme autochtone; histoire; histoire et politique; pol4105; premier cycle; périodes historiques; régions géographiques; science politique et droit; sciences humaines; sexualité; thématiques; travail

The Traditional Roles of Native Women in Canada and the Impact of Colonization - Brodribb, Somer (The Canadian Journal of Native Studies, 1984)
Recent trends in feminist research indicate a growing interest in the impact of Native women on westward expansion and imperialism. The author suggests that while early European contacts affected the status of women negatively, the views of Native women were seldom recorded during these early contact periods. Recent studies have examined the status and changing roles of Native women from the viewpoints of contemporary Native women. The diversity of their opinions continues to be a part of the contemporary debate on the resilience and resourcefulness of Native women in the past.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; 1970-1979; 1980-1989; amériques; approches et analyses; canada; cours; discipline; famille; féminisme autochtone; histoire et politique; intersectionnalité; mariage; pol4105; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; sexisme; sociologie; sofia; système colonial; systèmes d'oppressions; thématiques; violences

Marguerite : la traversée | Épisode 2 - Transistor média
Émilie Monnet trace des parallèles entre la vie de Marguerite Duplessis et la cause des femmes, et plus particulièrement des femmes autochtones. Accompagnée de ses invité·e·s, Émilie parle de la tragédie des femmes disparues et de l’objectification dont elles sont encore victimes aujourd’hui,...
Keywords: 1700-1799; 2000 à aujourd'hui; 2010-2019; 2020-2029; amériques; approches et analyses; arts; arts visuels et médiatiques; canada; cours; discipline; esclavage; féminisme autochtone; histoire et politique; justice sociale; martinique; performance; premier cycle; périodes historiques; québec; racisme; régions géographiques; sex2283; sexisme; système colonial; systèmes d'oppressions; thématiques; trafic sexuel; traite des femmes; violences; études littéraires